COMPARATIVE EVALUATION OF SURGICAL TREATMENT OF RIGID FLAT FEET IN CHILDREN WITH POSTERIOR TIBIALIS TENDON DYSFUNCTION - Шульга, Александр (SWorldJournal, 2021)
Summary. The rigid form of static flatfeet occurs in 18 to 20% of cases of the musculoskeletal system pathology. To date, no objective diagnostic methods have been developed, no algorithms for treating the rigid form of flatfeet depending on the severity,